Civil society at the millennium - Akuhata-Brown, Marcus; CIVICUS (Association) (West Hartford, Conn. : Kumarian Press, 1999)
"This publication documents how far civil society has come through the past decades and provides a good explanation of what its future role will be in the coming millennium. The thematic underpinnings of civil society examined in this book are globalization, governance, youth participation, women and leadership, sustainable development, religion, poverty, indigenous people, volunteering, and technology. The book strives to assess the health, viability, and role of civil society today and identify key challenges and opportunities facing civil society on a global scale."--BOOK JACKET.
11. Civil Society and Poverty: Whose Rights Count? / Caitlin Wiesen, Geoffrey D. Prewitt and Babar Sobhan -- 12. Coming Apart, Coming Together: Globalization and Civil Society / Isagani R. Serrano -- 13. From States to People: Civil Society and Its Role in Governance / Miklos Marschall -- 14. New Tools - Same Values: Information and Communication Technology to Support Civil Society / Liz Rykert -- 15. Civil Society at the Millennium / Kumi Naidoo and Rajesh Tandon.
Includes bibliographical references.
Nafisa
Keywords: Civil society